2016
DOI: 10.1097/bpo.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Capitellar Ossification Limits the Utility of the Radiocapitellar Line in Young Children

Abstract: Eccentric ossification of the capitellum explains RCL variability in young children. The RCL does not reliably intersect the central third of the ossified capitellum until ages 10 years in girls and 11 years in boys in the sagittal plane. The RCL should be used within its limitations in skeletally immature children and should be combined with advanced imaging if necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The model also showed that skeletal age affected the accuracy of the radiocapitellar line in males, with the line being more accurate as skeletal age increases. This shows that skeletal age, not chronological age [19], influenced the accuracy of the line, although there was no cut-off for age in our study where thereafter the line reliably bisected the capitellum, and our results were only limited to the male population.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The model also showed that skeletal age affected the accuracy of the radiocapitellar line in males, with the line being more accurate as skeletal age increases. This shows that skeletal age, not chronological age [19], influenced the accuracy of the line, although there was no cut-off for age in our study where thereafter the line reliably bisected the capitellum, and our results were only limited to the male population.…”
Section: Discussionmentioning
confidence: 60%
“…Ossification of the capitellum occurs from medial to lateral and is influenced by age and sex too. The eccentric nature of the ossification pattern of capitellum makes the reliability of the radiocapitellar line limited at a younger age, with the radiocapitellar line only reliably bisecting the capitellum after 10 years in girls and 11 years in boys [19]. This is supported by Kunkel et al .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies proved that in children with not fully ossified elbow joint, RCL misses capitulum in its middle third in up to 80% of cases and entirely in up to 17% of cases. 4 7 These studies also proved that RCL drawn through the neck of the radius is more accurate than the line drawn through the shaft. 3 , 4 This accentuates in younger children, which has been proven in this study, as only four of our patients from the group with suspected dislocation of the humeroradial joint were older than 10 years, and half of them (18) were younger than 6 years.…”
Section: Discussionmentioning
confidence: 70%
“…3,4 Despite regular use of RCL in diagnostics of the dislocation of the proximal radius, it has been proven that in younger children with unfinished ossification of the elbow, RCL misses the capitulum in its middle third or entirely. [3][4][5][6][7] This results mainly from the eccentric ossification of the capitulum and limits the use of RCL in assessing the humeroradial joint in younger children. If there is any doubt, a child with suspected dislocation of the proximal radius usually undergoes repeated X-rays and/or manipulation under an X-ray amplifier under general anesthesia to confirm the diagnosis.…”
Section: Introductionmentioning
confidence: 99%